Pyrolytic behaviors of Scenedesmus obliquus over potassium fluoride on alumina. (1st March 2020) - Yang, Changyan; Li, Rui; Qiu, Qi; Yang, Hui; Zhang, Youhong; Yang, Bohan; Wu, Jinsheng; Li, Bo; Wang, Wei; Ding, Yigang; Zhang, Bo
Graphical abstract: Highlights: The use of KF/Al2 O3 promoted the degradation of Scenedesmus and the formation of volatiles. Acidic pyrolysis products were minimized. The degradation of microalgal lipids, proteins, chlorophyll and choline was enhanced. KF/Al2 O3 selectively promoted cyclization reactions to produce more C3 -C10 cyclic organics. Abstract: Microalgae Scenedesmus species are widely utilized for sustainable biomass production. To develop microalgae conversion technology, catalytic pyrolysis of S. obliquus over the solid base catalyst of potassium fluoride on alumina (KF/Al2 O3 ) was investigated via thermogravimetric analysis (TGA), bench-scale experiments, and pyrolysis coupled with gas chromatograph/mass spectrometer (Py-GC/MS). The reaction variables included the pyrolysis temperature (450–650 °C) and the catalyst-to-microalgae ratio (1:10–1:1). TGA showed that KF/Al2 O3 could reduce the degradation temperature of this microalga and promote the formation of volatiles. The yield of non-condensable gases increased as the reaction temperature and the amount of the catalyst increased. The yield of solid residues was within a range of 19.5–36.5 wt%, while the liquid yield was between 41 and 45 wt%. A variety of important industrial product precursors, such as acetic acid, pyrrole, pyridine, benzyl nitrile, phenol, cresol, and indole, was formed during non-catalytic pyrolysis. KF/Al2 O3 catalyzed pyrolysis showed remarkable effects, including minimizing acidic products, redirecting the decomposition reaction of anhydrosugars, promoting degradation of microalgal lipids, proteins, chlorophyll and choline, selectively promoting cyclization reactions to produce more C3 -C10 cyclic organics, and enhancing dehydration reactions to form more nitriles.